Program Keluarga Harapan Dalam Peningkatan Kesejahteraan Masyarakat - Nur Praditya Djumura; Meyko Panigoro; Abdulrahim Maruwae; Irina Popoi (Universitas Negeri Gorontalo, 2022)
The study aimed to determine the effect of the Family Hope Program (PKH) on efforts to improve community welfare in Bubeya Village, Suwawa Subdistrict, Bone Bolango Regerency. It applied a quantitative method with a total of 60 respondents (local communities) in Bubeya Village. At the same time, the data analysis used simple regression analysis assisted by the SPSS program 17.0.The findings depicted that the Family Hope Program positively affected community welfare. Family Hope Program and community welfare equation were Ŷ = 14.292 + 0.358X. This regression model indicated that each increase of one (1) score in the Family Hope Program would be followed by an increase in community welfare for 0,358 at a constant of 14.292 with the R-squared (R2) value of 0,676 or 67.6%. This mean that the independent variable affected the dependent were not examined in while the remaining 32.4% was affected by other variables that were not examined in this study.